Post-Launch Public Interest in DeepSeek vs. ChatGPT: A Comparative Google Trends Analysis in Indonesia and the Philippines - Aridan, Muhammad; Irwandani; A. Villarama, Joseph; V. Dela Fuente, Abegail (WISE Pendidikan Indonesia, 2025)
This study investigates the post-launch public interest in DeepSeek and ChatGPT through a comparative analysis using Google Trends data from Indonesia and the Philippines. Employing a quantitative approach, the research examines temporal trends and regional variations to understand public engagement patterns with these AI tools. The findings reveal that ChatGPT consistently garners higher public interest in both countries, driven by its global recognition, multilingual capabilities, and extensive integration into educational and professional contexts. In contrast, DeepSeek shows sporadic increases in interest, particularly within niche communities and academic environments. The analysis highlights the influence of cultural, linguistic, and technological factors on AI adoption, emphasizing that while global brand strength supports widespread engagement, localized strategies are crucial for fostering sustained interest in emerging technologies. This study contributes to the understanding of AI adoption dynamics in Southeast Asia, offering insights for developers, educators, and policymakers to optimize AI integration in diverse socio-cultural contexts.